Orange Is the New Green: Exploring the Restorative Capacity of Seasonal Foliage in Schoolyard Trees - Paddle, Eli (MDPI, 2016)
Urban schoolyard environments are increasingly characterized by a proliferation of hard surfaces with little if any greenery. Schoolyard “greening” initiatives are becoming increasingly popular; however, schoolyard designs often fail to realize their restorative potential. In this quasi-experimental study, a proposed schoolyard greening project was used to visualize alternative planting designs and seasonal tree foliage; these design alternatives were subsequently used as visual stimuli in a survey administered to children who will use the schoolyard to assess the perceived restorative capacity of different design features. The findings indicate that seasonal changes in tree foliage enhance the perceived restorative quality of schoolyard environments. Specifically, fall foliage colour, when compared to green foliage, is rated as being perceived to be equally restorative for children. Additionally, seasonal planting, including evergreen conifers, may enhance the restorative quality of the schoolyard especially when deciduous trees are leafless. Landscape design professionals, community-based organizations, and other decision-makers in schoolyard greening efforts should strategically consider their tree choices to maximize year-round support for healthy attention functioning in children through restoration.